Nilai - Nilai Pendidikan Moral Islam Perspektif Habib Umar Bin Hafidz dan Habib Ali Al-Jufri - Halimatussadiah, Halimatussadiah; Rifqi Muntaqo; Ali Imron (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This study examines the concept of Islamic moral education according to Habib Umar Bin Hafidz and Habib Ali Al-Jufri, the methods of instilling moral values ​​that they use, and the relevance of their thoughts in the context of today's education. Moral education currently faces various complex challenges, such as weak role models, less applicable approaches, and the negative influence of technological advances and social media that trigger moral dilemmas among the younger generation. The lack of integration of moral values ​​in daily practice and the identity crisis due to globalization are also problems that hinder the formation of noble characters. The study used a qualitative approach with library research, collecting data from primary and secondary sources, then analyzed descriptively. The results of the study show that Habib Umar places love for Allah and the Messenger as the core of moral values, with educational methods that prioritize role models and gentleness without coercion, relevant to forming character and spirituality in the modern era. Meanwhile, Habib Ali emphasizes humanitarian values ​​such as compassion and tolerance as the foundation of moral education, with a moderate and inclusive approach that suits the needs of contemporary education. Both approaches provide important solutions in dealing with the problems of moral education, especially in building strong spiritual and social character amidst the dynamics of modern life, while also offering a foothold for overcoming the moral challenges faced by today's students.